TATA KELOLA RANTAI NILAI KOMODITAS JAGUNG DI PROVINSI GORONTALO - Qiki Qilang Syachbudy (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
Indonesia is still a corn importing country. However, Indonesia has the potential to become a global producer of corn. Gorontalo Province is an interesting area to study in terms of value chain governance for maize. Because, the government and the people of Gorontalo are able to make corn a commodity that has a comparative advantage in the region. Gorontalo's label as a corn producer is really well designed so that it sticks and is then able to improve the welfare of its people in general. The analytical method used in this study is to collect information from various sources, such as the Central Statistics Agency (BPS), journals, and research reports from related institutions. Furthermore, the information obtained is then analyzed according to the subject matter of value chain governance, namely in terms of the actors involved in value chain governance, the existence of lead firms, and in terms of upgrading. The results of the study indicate that there are still many things that need to be improved in value chain governance for maize commodities in Gorontalo Province. Some things that still become obstacles include the quality of corn that is not in accordance with industry needs; farmers who do not understand how to cultivate corn commodities properly and correctly; postharvest handling that is still traditional; and the weakness of supporting institutions at the farmer level. Things that require serious action in building the governance of the corn commodity value chain in Gorontalo Province is in terms of building a local lead firm in the livestock sector and animal feed industry.